2011
DOI: 10.1016/j.pec.2011.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the community pharmacist's role in palliative care: Focusing on the person not just the prescription

Abstract: ObjectivesChanges in health care provision have led to an emphasis on providing end of life care within the home. Community pharmacists are well positioned to provide services to communitybased palliative care patients and carers. MethodsA multiple qualitative case study design was adopted. A total of 16 focus groups and 19 interviews with pharmacists, nurses, general practitioners and carers were undertaken across metropolitan and regional settings in Western Australia, New South Wales, Queensland and Victori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 27 publications
3
38
0
1
Order By: Relevance
“…[9][10][11] Community pharmacists from urban and rural communities in Australia reported that they deliver palliative care services infrequently and consequently lack knowledge in this area. 12 Further, community pharmacists who dispense medications to home-based palliative care patients are often unfamiliar with uncommon palliative care medications 13 and often have misconceptions about opioid use. 14 In addition, research suggests that community pharmacists may be reluctant to be involved in palliative care.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] Community pharmacists from urban and rural communities in Australia reported that they deliver palliative care services infrequently and consequently lack knowledge in this area. 12 Further, community pharmacists who dispense medications to home-based palliative care patients are often unfamiliar with uncommon palliative care medications 13 and often have misconceptions about opioid use. 14 In addition, research suggests that community pharmacists may be reluctant to be involved in palliative care.…”
mentioning
confidence: 99%
“…14 In addition, research suggests that community pharmacists may be reluctant to be involved in palliative care. 12 Thus, any training should also work towards fostering positive attitudes towards their involvement in the palliative care interdisciplinary team. 15,16 Nurses' positive attitudes have been found to have a positive impact on both quality of patient care 17 and family participation in care, 18 as well as facilitating learning of factual knowledge.…”
mentioning
confidence: 99%
“…Pharmacists' expert pharmaceutical knowledge and broad skill set -coupled with their widespread accessibility and trusted relationships with patients and carers -mean that they are well suited to better integration within the palliative care team [22], [25] . The pharmacist's role is extending beyond the more traditional elements of dispensing activity and management of minor ailments towards the provision of greater psychosocial support for patients [22], [26] . This creates opportunities for further interaction, not only with patients, but also with loved ones, relatives and carers.…”
Section: Role Of the Pharmacist In Palliative Carementioning
confidence: 99%
“…This is an increasingly relevant topic in light of pharmacists' involvement in palliative care services both nationally and globally [21], [22], [23], [24], [25], [26] .…”
mentioning
confidence: 99%
“…Palijativna nega nije ograni膷ena samo na pacijente koji 膰e uskoro umreti, ve膰 otpo膷inje od trenutka postavljanja dijagnoze do smrti. Starenje populacije prozrokuje pove膰anje broja obolelih od hroni膷nih/啪ivotno ugro啪avaju膰ih bolesti, a posledi膷no i broja pacijenata koji zahtevaju palijativnu negu (3). Palijativna nega se sprovodi na svim nivoima zdravstvene za拧tite, i u ku膰nim uslovima (4).…”
Section: Uvodunclassified